2016
DOI: 10.1089/scd.2016.0244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secreted Molecules of Human Embryonic Stem Cell-Derived Mesenchymal Stem Cells on Acute Hepatic Failure Model

Abstract: Adult tissue-derived mesenchymal stem cells (MSCs) show tremendous promise for a wide array of therapeutic applications predominantly through paracrine activity. Recent reports showed that human embryonic stem cell (ESC)-derived MSCs are an alternative for regenerative cellular therapy due to manufacturing large quantities of MSCs from a single donor. However, no study has been reported to uncover the secretome of human ESCMSCs as treatment of an acute liver failure (ALF) mouse model. We demonstrated that huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 35 publications
0
73
0
Order By: Relevance
“…These inflammatory diseases include periodontitis, rheumatoid arthritis and inflammatory bowel disease ( 2 4 ). Patients suffering from inflammatory bone loss typically have an increased risk of morbidity and mortality, which may seriously impair their quality of life and thus cause a heavy economic burden ( 5 , 6 ). Therefore, intervention strategies through which inflammatory bone loss can be mitigated are highly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory diseases include periodontitis, rheumatoid arthritis and inflammatory bowel disease ( 2 4 ). Patients suffering from inflammatory bone loss typically have an increased risk of morbidity and mortality, which may seriously impair their quality of life and thus cause a heavy economic burden ( 5 , 6 ). Therefore, intervention strategies through which inflammatory bone loss can be mitigated are highly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of ECMs to develop efficient methods to isolate MSCs or mesodermal progenitor‐like cells from hESCs and hiPSCs remains largely unexplored. [ 2,5,11 ] Fibronectin, FN is a large ECM glycoprotein that triggers biochemical and mechanical signaling via integrin binding. Another hypothesis for the efficacy of this method is ECM remodeling in the earliest stages of embryonic development.…”
Section: Resultsmentioning
confidence: 99%
“…Representatively, selected small‐molecules, [ 6 ] spontaneously differentiating embryoid bodies (EBs), [ 2,7 ] cytokine/growth factor combinations, [ 8,9 ] coculturing systems, [ 10 ] and fluorescence‐activated cell sorting (FACS) after MSCs derivation/differentiation [ 2,5 ] have been reported. In addition, simplified techniques using physical cues, such as biomimetic fibrillar collagen, [ 5 ] gelatin, [ 2 ] and Matrigel, [ 2,11 ] have been utilized to derive MSCs from PSCs. However, unfortunately, the efficient and simplified methods are yet to be fully established to overcome the limitations of previous methods.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence showed that MSCs secretions exerted a bene cial effect by reducing the in ammatory response, promoting the survival and proliferation of injured cells, and ameliorating liver injury. (21,(44)(45)(46)(47) In the present study, microcapsules were used as carriers to encapsulate UMSCs and hepatocytes to persistently release the secretory factors contributing to the repair of impaired liver and the reduction of in ammatory response in ALF. And more, HNF4α-UMSCs signi cantly argument the therapeutic effects on ALF mice (Fig.1-5).…”
Section: Discussionmentioning
confidence: 99%